2015
DOI: 10.1111/jsr.12289
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and risk of Parkinson's disease: a population‐based cohort study

Abstract: Summary Sleep disorders could be associated with neurodegenerative diseases. This study aimed to determine the risk of Parkinson's disease in patients with obstructive sleep apnea. The incident cases of newly diagnosed obstructive sleep apnea were identified between 2000 and 2009 from the medical claims database of National Health Institute of Taiwan. The risk of Parkinson's disease onset at least 1 year after the diagnosis of obstructive sleep apnea was measured during and up to 11 years of period, compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 25 publications
1
29
1
Order By: Relevance
“…Several studies have reported that SA is associated with subsequent PD 3335. However, the present study findings were different and had stronger implications than those of previous studies.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Several studies have reported that SA is associated with subsequent PD 3335. However, the present study findings were different and had stronger implications than those of previous studies.…”
Section: Discussioncontrasting
confidence: 97%
“…Fourth, because of the relatively short follow-up period of 3 years, it was difficult to determine whether SA occurred during the prodromal phase of PD before the onset of motor symptoms. Previous studies with longer follow-up periods have supported our findings, despite using different inclusion and exclusion criteria 3335. Fifth, the actual number of patients with SA who developed PD was small, particularly in women and young patients, thus limiting the statistical power in subgroup analysis based on age and sex.…”
Section: Discussionsupporting
confidence: 73%
“…The OSA symptoms in patients with PD do not appear to be good predictors of non-motor PD symptoms, such as depressive symptoms, fatigue, cognitive impairment, daytime sleepiness and overall quality of life (Cochen De Cock et al, 2010;Neikrug et al, 2013). An increased risk for developing PD in patients with OSA was reported in a series of Taiwanese studies with 5-11 years follow-up (Chen, Tsai, Li, & Hwang, 2015;Yeh, Tien, Yang, Wang, & Weng, 2016), although in one study the difference was found only for women (Sheu, Lee, Lin, Kao, & Chung, 2015). ).…”
Section: Sleep-related Breathing Disordersmentioning
confidence: 88%
“…Recently, two population-based studies from Taiwan assessed the risk for developing Parkinson's disease in patients with OSA [64,65]. The incidence of Parkinson's disease in the OSA cohort was approximately two times higher than that in individuals without OSA with women aged 50-69 and individuals with insomnia being at high risk [64].…”
Section: Sleep Disordered Breathingmentioning
confidence: 99%